Effectiveness of Biopesticides Based on Local Endophytic Microorganisms against Spodoptera frugiperda Pests in Corn Plants: Efektivitas Biopestisida Berbasis Mikroorganisme Endofit Lokal terhadap Hama Spodoptera frugiperda pada Tanaman Jagung - Ngabito, Afrianti Ngabito; Rosita, Mila (Universitas Widya Gama Mahakam, 2025)
This study aims to analyze the effectiveness of biopesticides based on local endophytic microorganisms as an environmentally friendly alternative in controlling Spodoptera frugiperda pests in corn plants. The study was conducted using a qualitative approach based on library research, reinforced by field data from previous studies and simulations of comparative field tests between endophytic biopesticide treatments and chemical pesticides. Data were analyzed descriptively and comparatively by reviewing control effectiveness, crop productivity, and the environmental efficiency index (EI). The results showed that endophytic biopesticides containing isolates of Bacillus subtilis and Trichoderma harzianum were able to reduce the intensity of S. frugiperda attacks by up to 65.8%, approaching the effectiveness of synthetic chemical pesticides (79.4%). In addition, the endophytic biopesticide treatment produced an average harvest of 7.42 tons/ha with an EI of 0.92, indicating a much lower ecological impact compared to chemical pesticides (EI of 0.45). These results indicate that local endophytic biopesticides are agronomically effective, environmentally safe, and have great potential for application in integrated pest management (IPM) systems in corn cultivation in Indonesia.